Handbook of alternative fuel technologies - Lee, Sunggyu; Speight, James G.; Loyalka, S. K. (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'This book focuses on the different intermediates and raw material options that can generate energy output and products equivalent to conventional petroleum sources. It presents short-term options for clean alternative energy sources that complement the development of long-term sustainable energy infrastructures. Detailing the chemical processes for each technology, the text also assesses the environmental impact, benefits, and performance of the various processes and fuel products. It also summarizes processing and transportation issues, safety concerns, regulations, and other practical considerations associated with alternative fuels'--
'Energy has always been the foremost important resource upon which humans have relied for survival and productive activities. Industrialization and technological advancement of modern society have also been possible through the effective use of energy. There is a strong correlation between the index for quality of life and energy consumption. Heightened economic strength of a country, technological prosperity of a society, higher production output of an industry, improved finances of a household, and increased activities of an individual are also realized by effective utilization of energy'--
First publish by author Sunggyu Lee.
Includes bibliographical references and index.
Includes index.
Keywords: Fuel -- Handbooks, manuals, etc; Fuel switching -- Handbooks, manuals, etc; Power resources -- Handbooks, manuals, etc